Effect of gamma irradiation on egg hatchability, adult survival and longevity of the mango pulp weevil, Sternochetus Frigidus (fabr.) - Obra, Glenda B.; Resilva, Sotero S.; Lorenzana, Louella Rowena J. (2017)
The effect of irradiation on egg hatchability, adult survival and longevity of Sternochetus frigidus (Fabr.) was studied using different doses of gamma radiation. Irradiation lowered egg hatchability, longevity and survival rates of S. frigidus. Response of males and females in terms of longevity and survival rates differed at sub-efficacious and efficacious doses. The study shows that the use of phytosanitary irradiation against S. frigidus results in a lowered risk that adults would be detected by survey programs as irradiation at doses resulting from commercial phytosanitation reduces longevity drastically, and that use of radiation induced sterility for SIT may not possibly work on this pest. (Author's abstract)